2006
DOI: 10.1080/03009480600781958
|View full text |Cite
|
Sign up to set email alerts
|

Late Pleistocene glacial and lake history of northwestern Russia

Abstract: Five regionally significant Weichselian glacial events, each separated by terrestrial and marine interstadial conditions, are described from northwestern Russia. The first glacial event took place in the Early Weichselian. An ice sheet centred in the Kara Sea area dammed up a large lake in the Pechora lowland. Water was discharged across a threshold on the Timan Ridge and via an ice‐free corridor between the Scandinavian Ice Sheet and the Kara Sea Ice Sheet to the west and north into the Barents Sea. The next … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 135 publications
(187 citation statements)
references
References 59 publications
5
179
2
1
Order By: Relevance
“…2). Glacigenic deposits comprising till, fluvial and lacustrine sediments of the Late Weichselian Scandinavian glaciation dominate subsurface exposures in the western part of the discussed region, whereas the areas to the east were glaciated by the Barents and the Kara ice sheets in Early and Middle Weichselian time Larsen et al 2006a). A comprehensive review of previous investigations in northwestern Russia has been provided by Demidov et al (2004).…”
Section: Settingmentioning
confidence: 99%
“…2). Glacigenic deposits comprising till, fluvial and lacustrine sediments of the Late Weichselian Scandinavian glaciation dominate subsurface exposures in the western part of the discussed region, whereas the areas to the east were glaciated by the Barents and the Kara ice sheets in Early and Middle Weichselian time Larsen et al 2006a). A comprehensive review of previous investigations in northwestern Russia has been provided by Demidov et al (2004).…”
Section: Settingmentioning
confidence: 99%
“…From a geomorphological perspective, we note for example that moraines located outside the inferred Weichselian (Valdaian) limit (Larsen et al, 1999, p. 32;Svendsen et al, 2004, p. 56) appear to be more degraded by fluvial-and permafrost activity. Elsewhere, we note that revisions to the reconstructions of Larsen et al (1999), Larsen et al (2006) and might be needed, which is also supported by (Kalm, 2012, p. 23). Most notably in the Severnaya Dvina to Vologda area, our mapping suggests that the Last Glacial Maximum ice sheet extended about 150 km further east than previously thought (Lyså et al, 2011) (Figure 3).…”
Section: Moraine Morphology Distribution and Agementioning
confidence: 51%
“…23,000 km 3 ; [48]). Terrestrial fieldwork revealed a complex history of buildup and decay of the Eurasian ice masses during the last *200 ky (Svendsen et al [81]; Larsen et al [47]). Whenever these ice sheets decayed, pathways opened which allowed for the freshwater to enter the Arctic Ocean (Fig.…”
Section: Weichselian and Saalian Glaciationsmentioning
confidence: 99%